There is More to 'Making Connections to Improve Health Outcomes' - Joachim Sturmberg MBBS, MFM, DORACOG, FRACGP, PhD (SAGE Publishing, 2022)
Langevin 1 rightly points to the reductionist mindset being the stumbling block for providing person-centered care. While considering the interconnections between the various domains underpinning health is a necessary first step towards more person-centered care, it ultimately is not sufficient. Person-centered care arises from the appreciation of the interdependencies and interactions between the various domains across its large-scale supersystems as much as its small-scale subsystems. Viewed with a complex-adaptive systems mindset health and disease are the phenotypical outcome categorisations of a person's whole-of-systems dynamics across all scales of organisation. 2 , 3